Supplementation with myo-inositol and Selenium improves the clinical conditions and biochemical features of women with or at risk for subclinical hypothyroidism - Payer, Juraj; Jackuliak, Peter; Kužma, Martin; Džupon, Matúš; Vaňuga, Peter (Frontiers in Endocrinology, 2022)
Purpose The present study aims to evaluate the effect of myo-Inositol plus Selenium supplementation in patients affected by subclinical hypothyroidism. Methods One hundred and forty-eight patients were included in the study from 8 different centers of Slovakia, and treated for 6 months with a daily dose of 600 mg myo-Ins plus 83 mcg Se. The patients included at the enrollment were women of reproductive age (18-50), who exhibit values of TSH in the range 2.5-5 mU/l and positivity to antibodies TPO-Ab/TG-Ab, or otherwise values of TSH in the range 5-10 mU/l both with and without positivity to antibodies TPO-Ab/TG-Ab. Results Patients affected by subclinical hypothyroidism exhibited a significant improvement of their condition when treated for 6 months with a combination of myo-Inositol and Selenium. The TSH values significantly ameliorated along with the index of autoimmunity and the thyroid status. In a sub-class of patients, the auto-antibody titer decreased after myo-inositol + Selenium administration. The treatment also induces a regularization of the menstrual cycle and a reduction of the cholesterol in the patients enrolled for the study. Furthermore, a significant improvement is observed in the perception of the symptoms associated with subclinical hypothyroidism over the treatment period. Conclusion A dietary supplementation with of myo-Inositol and Selenium in the treatment of patients affected by subclinical hypothyroidism exhibits a beneficial role in the recovery of TSH values, in the improvement of the symptoms associated to this condition and in the maintenance of the thyroid functions. The trial was approved by the Ethical Committee from National Institute of Endocrinology and Diabetology of Lubochna, Slovakia, date 18.12.2018, registration number: 3124/2018.